KARAKTERISTIK TINDAK PIDANA TERORISME DI INDONESIA - Wiwik Afifah (Yayasan Akrab Pekanbaru, 2019)
Indonesia as a state of law in accordance with the mandate of the constitution, was built into a democratic state that is equipped with human rights. However, in the course of the State, including extremist groups who carry out terror in the interests of certain groups. The number of terrorism cases as part of a crime needs attention in asking for their characteristics, models and forms. This is useful for the community and law enforcement to carry out prevention, anti-terror and handling efforts. This writing uses the normative juridical method. The results of this study have emerged many diverse characteristics of terrorism, consisting of individuals and groups, businesses, to religious, modern, and heroic oriented. Search for what is meant by activating online search, opening up the structure of the State, religious approach to modern life. The author of education-related forms of the entry of terrorism and the State of spending and coaching constantly in existence so as not to return to active agents who commit terror.